Let's denote Cassandra's younger brother's height as \( x \) inches.
According to the information given:
- Cassandra's height is \( 63 \) inches.
- This height is \( 6 \) inches less than \( 3 \) times her brother's height.
We can write the relationship as an equation:
\[ 63 = 3x - 6 \]
Now, rearranging this equation into the form \( px + q = r \):
-
Start with the equation: \[ 3x - 6 = 63 \]
-
Add \( 6 \) to both sides: \[ 3x = 63 + 6 \] \[ 3x = 69 \]
Thus, we can express this in the equation format \( px + q = r \): \[ 3x - 69 = 0 \]
So the equation that represents this problem in the form \( px + q = r \) is:
\[ 3x - 69 = 0 \]
Now, you can solve for \( x \) (the height of her younger brother): \[ 3x = 69 \implies x = \frac{69}{3} = 23 \]
Therefore, Cassandra's younger brother is \( 23 \) inches tall.